PENGENDALIAN KUALITAS PRODUKSI TEH TB 4 ASLI RCLT MENGGUNAKAN METODE SEVEN TOOLS PADA PT. XYZ - Danang Prihandoko; Esta Fania; Jihan Nurul Julita (Pascasarjana Universitas Halu Oleo, 2020)
PT. XYZ often experiences production constraints because of the tea TB 4 Asli RCLT's type of defective product during the production process. The purpose of this study is to find out the factors that cause the occurrence of defective products and provide recommendations that can be made to reduce the level of defective products. This study uses the Seven Tools method which consists of flow charts, check sheets, histograms, pareto diagrams, scatter diagrams, fish bone diagrams (cause-and-effect diagrams), and statistical process control (control charts). The results showed that there were 2 types of the biggest defects are Bag Overlap with a damage percentage of 26.15% and Tea in Seal 22.56%. These defects are caused by several major factors which are machines and men. The results of the study also show that the company's production process is still not well controlled. So, it is expected that PT. XYZ considers recommendations by giving more attention to the quality of the people who work and conducting in-depth analysis of other factors that can cause engine damage so that the company can reduce the level of defective products during the production process.